A prospective observational study on correlation between the BMI of pregnant women and materno-fetal outcome - Agrawal, Divyani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Body Mass Index (BMI) during pregnancy is crucial to stipulate health risks. High pre-pregnancy BMI and/or excessive weight gain during pregnancy has negative implications on pregnancy outcomes, putting the health of mother and infant at risk also it amplifies the burden of chronic disease. Hence, public initiatives aiming in reduction of maternal and fetal morbidity and mortality can be vitalised by identification of high-risk population based on BMI leading to implementation of targeted interventions, such as nutritional counselling, weight management programs, and close monitoring during pregnancy. Methods: This prospective observational study was conducted over a period of over 10months of duration from January 2025 to October 2025 among 500 pregnant women coming to ANC OPD who fulfilled the selection criteria and agreed to participate in study. The study aimed to assess the feto-maternal outcomes in pregnant women of different BMI categories. Results: Out of 500 pregnant females, majority of pregnant females were in normal BMI category 59% (295) while rest were underweight 13% (65), overweight 22% (110), and obese 6% (30). The antenatal and postnatal complications were more in overweight and obese patients in comparison to normal weight and underweight. Also, the instrumental delivery and lscs rate were higher among the women with high BMI. Conclusions: In developing countries like India both underweight and obesity poses a significant impact on the outcome of pregnancy. Achieving an optimal weight gain for every pregnant woman is the basis for the development of a healthy population and an essential factor in the physiological course of pregnancy and childbirth and thus contributing to reduction in maternal and fetal mortality and morbidity.